2011
DOI: 10.3892/ijo.2011.1056
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and biological significance of CDC28 protein kinase regulatory subunit 2 overexpression in human gastric cancer

Abstract: Abstract. CDC28 protein kinase regulatory subunit 2 (CKS2)is a cyclin-dependent kinase subunit (cKS) family member that participates in cell cycle regulation. Few studies have investigated its involvement in gastric cancer. In this study, we focused on the clinical and biological significance of CKS2 overexpression in gastric cancer. The expression of CKS2 mRNA was studied by real-time quantitative reverse transcription polymerase chain reaction, and the expression status in each tumor was examined to varify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Of the 116 genes highly expressed in the C2 subtype, 22 were associated with these GO terms and KEGG pathways, most of which are implicated in cancer: Ribosomal protein (RP)-encoding genes RPL6 , RPLP0 , RPL8 , RPS6P1 , PRS7 , and RPL29 [9], eukaryotic translation elongation factor EEF1B2 [10], eukaryotic translation initiation factor EIF5A [11], mRNA export factor THOC4 [12], heterogeneous nuclear ribonucleoprotein HNRNPA1 [13], mitotic arrest deficiency 2 MAD2 [14], proteasome subunits PSMA6 and PSMB8 [15], protein kinase regulatory subunit CKS2 [16], and PDZ-binding kinase PBK [17]. These results suggest that altered expression of these identified genes could reflect the specific molecular and biological features of gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 116 genes highly expressed in the C2 subtype, 22 were associated with these GO terms and KEGG pathways, most of which are implicated in cancer: Ribosomal protein (RP)-encoding genes RPL6 , RPLP0 , RPL8 , RPS6P1 , PRS7 , and RPL29 [9], eukaryotic translation elongation factor EEF1B2 [10], eukaryotic translation initiation factor EIF5A [11], mRNA export factor THOC4 [12], heterogeneous nuclear ribonucleoprotein HNRNPA1 [13], mitotic arrest deficiency 2 MAD2 [14], proteasome subunits PSMA6 and PSMB8 [15], protein kinase regulatory subunit CKS2 [16], and PDZ-binding kinase PBK [17]. These results suggest that altered expression of these identified genes could reflect the specific molecular and biological features of gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The caspase family of proteins play a critical role in mediating cellular apoptosis. It has been reported that Cks2 downregulation reduces cell proliferation and increase caspase-3 activation and Bax expression in gastric cancer cells ( 6 ). Depleting Cks2 expression with siRNA in esophageal squamous cell carcinoma also results in reducing cell proliferation ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDK regulatory subunit 2 (CKS2) is overexpressed and associated with aggressiveness of many human malignancies, including cancer of the uterine cervix, prostate, gastrointestinal tract, bile duct, breast, and liver [1], [2], [3], [4], [5], [6], [7], [8], [9]. In cervical cancer, high CKS2 expression has been associated with presence of lymph node metastases at diagnosis and poor survival following chemoradiotherapy [2].…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, high CKS2 expression has been associated with presence of lymph node metastases at diagnosis and poor survival following chemoradiotherapy [2]. Overexpression of CKS2 in cell lines from a variety of cancer types has been shown to promote cell proliferation, whereas CKS2 knockdown induced cell cycle arrest and apoptosis and inhibited cell growth, migration, and tumorigenesis in mice [1], [3], [6], [9], [10]. CKS2 has therefore been suggested as a new candidate biomarker and therapeutic target; however, a better understanding of its role in cancer pathogenesis is required before the findings can be fully exploited in the clinic [11].…”
Section: Introductionmentioning
confidence: 99%